First records of the myrmecophilous spider Thyreosthenius biovatus (O. Pickard-Cambridge, 1875) for Slovenia and new Slovenian records for the myrmecophilous spider Mastigusa arietina (Thorell, 1871) - Gregor Bračko; Rok Kostanjšek (Natura Sloveniae)
Ants from the Formica rufa group, also known as red wood ants, build large mound nests and play an important role in their environment, especially in forests. Their nests harbour a species rich and abundant myrmecophilous fauna, including a few European spider species. Myrmecophilous spiders in 40 nests of red wood ants from 25 sites were searched for in Slovenia. In each mound nest, four to five litres of material were collected, which were placed in a sifter, with the sifted material examined for the presence of spiders. Two myrmecophilous spider species were found in the nests: Thyreosthenius biovatus (fam. Linyphiidae), representing first records for Slovenia, and Mastigusa arietina (fam. Cybaeidae), previously known from several sites in western Slovenia, but never purposefully searched for in ant nests. The first spider species was found in half of the examined nests, belonging to all sampled species of red wood ants, most of them to F. aquilonia, and M. arietina was detected in 37.5% of the examined nests, belonging to F. aquilonia and F. lugubris. The two spider species are presumably not rare in Slovenia, especially in the areas with a high number of red wood ant nests.